Future spatial and temporal variation of blue and green water in the Jing River Basin of central China under changing climatic conditions - Zhan, Yangying; Li, Chunyi; Tang, Jun; Ning, Yu; Fan, Guiying; Deng, Liting; Ma, Hua (Frontiers in Environmental Science, 2024)
The blue and green water resource distribution of the Jing River Basin, a cradle of Chinese civilization on the Loess Plateau, was studied using the Soil and Water Assessment Tool and the Sequential Uncertainty Fitting algorithm (vers. 2). Understanding these resources aids in the ecological preservation of the Yellow River Basin and its high-quality development. Future climate conditions were simulated using the Statistical Downscaling Model (SDSM). The data came from the Shared Socioeconomic Pathway (SSP) projections (SSP1-2.6, SSP2-4.5, and SSP5-8.5) in the Canadian Earth System Model (vers. 5), covering the 2030s, 2060s, and 2090s (based on 2015–2045, 2046–2075, and 2076–2100 climate projections, respectively). The SDSM accurately simulated temperature and precipitation trends, with its temperature predictions being more accurate. The results show that the maximum temperature, minimum temperature, and precipitation tend to increase under the three future climate scenarios, and the amount of blue and green water continues to increase in the future, with the SSP5-8.5 scenario showing the highest amount of blue and green water, and the SSP1-2.6 scenario showing the lowest amount of blue and green water, in terms of the climate scenarios. In terms of temporal distribution, 2090s has the most abundant blue and green water and 2030s has the least blue and green water content. Forecasting blue and green water changes due to climate change is vital for regional water management and risk assessment.